Si Orange, Effervescent Wortel sebagai Rintisan Technopreneur Mahasiswa Berbasis Bahan Baku Lokal - Kuncahyo, Ilham; Soebiyanto, Soebiyanto; Atmoko, Waluyo Budi; Sumardiyono, Sumardiyono; Mahayana, Argoto; Sunardi, Sunardi (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Vitamin A deficiency is the leading cause of blindness worldwide, and can affect anyone, especially pregnant women and children in developing countries like Indonesia. One of the abundant sources of vitamin A is carrots. However, children often find it difficult to eat vegetables, especially carrots. For this reason, it is necessary to try a way to make children interested and to consume carrots. Students at Setia Budi University were moved to produce effervescent carrot products through the Entrepreneurial Student Group (KMW). KMW is trying to produce food for health, namely carrot effervescet brand Si Orange. KMW Si Orange has tried to produce carrot effervescent. The conclusion of this activity is that KMW Si Orange has succeeded in producing and marketing carrot effervescent products that are practical, delicious and efficacious which have the advantage of being made from carrots and containing provitamin A, in the form of effervescent powder to overcome the problem of vitamin A deficiency.